Sensory Profiling and Consumer Acceptance of Pasta, Bread, and Granola Bar Fortified with Dried Olive Pomace (Pâté): A Byproduct from Virgin Olive Oil Production. Issue 10 (23rd September 2019) - Cecchi, Lorenzo; Schuster, Noah; Flynn, Dan; Bechtel, Rose; Bellumori, Maria; Innocenti, Marzia; Mulinacci, Nadia; Guinard, Jean‐Xavier
Abstract : Abstract: An olive pomace (pâté) obtained from virgin olive oil production, was used for the fortification of pasta, bread, and granola bar. For each food, a control (without pâté) and a fortified sample (with pâté, 7% in pasta and 5% in bread and granola bar) were manufactured. Descriptive analysis showed that pâté strongly affected the appearance of pasta and bread and increased the bitterness of bread and granola bar but not pasta. Granola bar was less affected in general, likely because of its higher ingredient complexity. In a central location test with 175 Californian consumers, both the control and the fortified samples of all three foods were well accepted overall, with only the mean liking of the appearance of the fortified pasta falling below the "neither like nor dislike" mark. Approximately 30% of consumers preferred the fortified sample over the control for each food and 50% were willing to pay more for the fortified products. The percentage of phenols from pâté recovered in the prepared samples was such that 63 g of pasta, 18 g of bread, and 12 g of granola bar would be sufficient to meet the EFSA health claim for olive oil phenols. This study demonstrates that pâté can be used for fortification of foods for human consumption, thus adding potential economic value to the virgin olive oil production chain and allowing for a higher daily intake of phenols from Olea europaea L., whose beneficial health properties are well recognized. Practical Application: The dried olive oil pomace (pâté) that we developed and tested in this research can be used to fortify pasta, bread, and granola bars with health‐beneficial phenols with only slight alterations of their sensory profiles and slight reduction in consumer acceptance. Virgin olive oil producers can use this byproduct and gain further economic value from olive oil production.